Building terrorism resistant communities : together against terrorism - Ekici, Sıddık (NATO science for peace and security series. Human and societal dynamics ;, 2009)
Intends to explore methods to involve the community in the fight against terrorism in an effort to enhance its protection from terrorist attacks and to establish a network between the participants for future collaborations. This guide can help policy makers gain an understanding of how counter terrorism requires community support and involvement.